A study on fouling during harvesting of Chlorella vulgaris using microfiltration / Nadia Hazwani Mohd Nasir - Nadia Hazwani, Mohd Nasir (2018)
Microalgae harvesting using membrane filtration is economically attractive and does not require any addition of chemicals. Membrane filtration has a major drawback related to membrane fouling that can be minimized by controlling filtration hydrodynamic parameters. The effect of hydrodynamic control is only secondary compared to the fouling materials existed in microalgae culture. A few recent studies have found that one of the microalgae components, transparent exopolymer particle (TEP) is a key factor causing fouling. Understanding TEP production in microalgae culture is important to reduce membrane fouling phenomena. In this study, Chlorella vulgaris was cultivated in a batch pure culture using 5L closed bubbled column PBR to investigate its physiological state during its growth phase cycle. Fouling caused by TEP was studied during microfiltration (MF) of C. vulgaris at their physiological ages of 2, 4, 6, 8, and 10 days. MF was conducted at constant operation condition consists of 0.5 bar transmembrane pressure (TMP) and 2.13 m/s crossflow velocity (CFV) using titanium oxide tubular membrane with pore size of 0.45 μm. During the growth cycle, TEP production from C. vulgaris was low during exponential growth phase then suddenly rose towards stationary phase and highly accumulated until its senescence phase. The highest amount of TEP concentration accumulated was 0.31 g/L during microalgae cultivation of 14d. The fouling phenomena was determined using modified fouling index (MFI) and resistance factor. The highest MFI value is 11.49 x 105 sL-2 during filtration on 6d microalgae physiological age. Pore blocking resistance (Rb) has the highest value at 5.43 x 1012 m-1 during MF of 6d microalgae physiological age. TEP concentration gave significant influence to Rb but MFI values showed that high total biomass concentration influence cake resistance (Rc) that caused severe fouling.